MENYIKAPI TANTANGAN PENDIDIKAN DI INDONESIA: SOLUSI INKLUSIF MELALUI ANALISIS KEBIJAKAN - Gunawan, Reski; Bedi, Fisman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The issue of educational policy in Indonesia has become a major concern in efforts to improve human resource quality and global competitiveness. This article aims to analyze the issues of educational policy in Indonesia through a literature review approach. The study identifies key problems such as disparities in educational access, teaching quality, and curriculum relevance to labor market needs. By reviewing various literatures from journals, reports, and academic sources, this article offers a new perspective to formulate more inclusive and adaptive policies. The findings show that educational policies integrated with technology and tailored to local needs have significant potential to enhance the effectiveness of the educational system.